2020
DOI: 10.3390/cells9040988
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Circulating Endoglin in Hypertension via the Upregulated Expression of BMP4

Abstract: Endoglin is a membrane glycoprotein primarily expressed by the vascular endothelium and involved in cardiovascular diseases. Upon the proteolytic processing of the membrane-bound protein, a circulating form of endoglin (soluble endoglin, sEng) can be released, and high levels of sEng have been observed in several endothelial-related pathological conditions, where it appears to contribute to endothelial dysfunction. Preeclampsia is a multisystem disorder of high prevalence in pregnant women characterized by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 82 publications
(130 reference statements)
2
26
0
Order By: Relevance
“…The presence of high circulating levels of sEng in preeclampsia has been widely described, and therefore it has been proposed as an early diagnostic and prognostic biomarker of this disease [ 18 , 44 , 45 ]. Moreover, several studies in animal models have demonstrated that increased plasma levels of sEng could play a pathogenic role in preeclampsia [ 14 , 18 , 24 , 26 ]. However, the animal models used up to date might not be wholly representative of the actual disease, as the symptoms associated with increased plasma levels of sEng in those models were not dependent on gestation, and only phenocopied the so-called second step of the disease, related to the systemic mother’s response and associated clinical symptoms [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of high circulating levels of sEng in preeclampsia has been widely described, and therefore it has been proposed as an early diagnostic and prognostic biomarker of this disease [ 18 , 44 , 45 ]. Moreover, several studies in animal models have demonstrated that increased plasma levels of sEng could play a pathogenic role in preeclampsia [ 14 , 18 , 24 , 26 ]. However, the animal models used up to date might not be wholly representative of the actual disease, as the symptoms associated with increased plasma levels of sEng in those models were not dependent on gestation, and only phenocopied the so-called second step of the disease, related to the systemic mother’s response and associated clinical symptoms [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our results suggest that the contribution of high levels of sEng to the preeclampsia phenotype is not immediate but needs a sustained increase of plasma sEng. Interestingly, we recently described that sEng induced the expression of BMP4 which, in turn, mediated the sEng-dependent effect in hypertension [ 26 ]. The existence of this intermediate may account for the observed delay between the appearance of increased plasma sEng levels and an increase in blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another cell surface receptor that yields a soluble form involved in cardiovascular pathophysiology is endoglin, a glycoprotein primarily expressed by the vascular endothelial cells. Gallardo Vara et al study the relationship of soluble endoglin (sEng) with hypertension in preeclampsia, and using a combination of cellular and animal models find BMP4 as a downstream mediator of sEng effects [ 12 ]. Once again, these results show that circulating forms from proteolytically processed membrane-bound proteins are common in cardiovascular pathology, and can be useful as biomarkers to monitor the activation of key pathophysiological pathways involved in disease progression [ 13 ].…”
mentioning
confidence: 99%